Discovery of non‐HLA antibodies associated with cardiac allograft rejection and development and validation of a non‐HLA antigen multiplex panel: From bench to bedside. Issue 10 (26th April 2020) - Butler, Carrie L.; Hickey, Michelle J.; Jiang, Ning; Zheng, Ying; Gjertson, David; Zhang, Qiuheng; Rao, Ping; Fishbein, Gregory A.; Cadeiras, Martin; Deng, Mario C.; Banchs, Hector L.; Torre, Guillermo; et al.
Abstract : We analyzed humoral immune responses to nonhuman leukocyte antigen (HLA) after cardiac transplantation to identify antibodies associated with allograft rejection. Protein microarray identified 366 non‐HLA antibodies (>1.5 fold, P  < .5) from a discovery cohort of HLA antibody–negative, endothelial cell crossmatch–positive sera obtained from 12 cardiac allograft recipients at the time of biopsy‐proven rejection. From these, 19 plasma membrane proteins and 10 autoantigens identified from gene ontology analysis were combined with 48 proteins identified through literature search to generate a multiplex bead array. Longitudinal sera from a multicenter cohort of adult cardiac allograft recipients (samples: n = 477 no rejection; n = 69 rejection) identified 18 non‐HLA antibodies associated with rejection ( P  < .1) including 4 newly identified non‐HLA antigenic targets ( DEXI, EMCN, LPHN1, and SSB ). CART analysis showed 5/18 non‐HLA antibodies distinguished rejection vs nonrejection. Antibodies to 4/18 non‐HLA antigens synergize with HLA donor‐specific antibodies and significantly increase the odds of rejection ( P  < .1). The non‐HLA panel was validated using an independent adult cardiac transplant cohort (n = 21 no rejection; n = 42 rejection, >1R) with an area under the curve of 0.87 ( P  < .05) with 92.86% sensitivity and 66.67% specificity. We conclude that multiplex bead array assessment of non‐HLA antibodies identifies cardiac transplant recipients at risk of rejection. Abstract : Using high throughput proteomics and bioinformatics, the authors report the discovery and validation of a novel panel of nonhuman leukocyte antigens that can identify antibodies associated with cardiac allograft rejection. An editorial from Jackson and Glass is on page 2639 .